(untitled) (Interdisciplinary Journal of Education Research, 2022)
English Foreign Language (EFL) teachers most frequently deal with question types in their interactions with students. However, questioning is not only concerned with type but also with form and function. Therefore, this qualitative study aimed to examine the types, forms, and functions of the questions altogether raised by EFL teachers as they interacted with students. The researcher observed and recorded two college-level EFL teachers. Using the conversation analysis tenets, the data were transcribed and examined. The results have demonstrated that the teacher questions used were insufficient for the questioning activity. The form is related to the question type. Additionally, the teachers’ questions had diagnostic, educational, and motivating purposes. Therefore, it is advantageous for teachers to ask questions during class discussions if they have a comprehensive understanding of type, shape, and function.